Emotional intelligence’ among secondary school teachers in Bahri locality - Ahmed, Ghada Alameen (Journal of Educational and Psychological Sciences, 2023)
The study aims at finding out the availability of components of ‘emotional intelligence’ among secondary school teachers in Bahri locality. The study sample are 151 randomly chosen males and females- secondary school teachers working at Bahri locality for the academic year 2022- 2023. The study follows a descriptive approach designing and distributing a (47 statements) questionnaire, to collect data about the availability of the five dimensions of the ‘emotional intelligence components’. The study proves that the availability degree of ‘emotional intelligence’ components among secondary school teachers at Bahri locality is generally ‘high’ within an arithmetic Mean of (3.85). The factors appears in the following order: ‘empathy’ achieves the first stage, followed by ‘self- awareness’, social skills, preacher, and the least is ‘self- regulation’ factor. The study also reveals apparent differences between the arithmetic averages of the study subjects’ responses to the statements gauging the degree of availability of ‘emotional intelligence’ components. The differences are for the male participants achieving a higher arithmetic average compared to females on all factors as well as the total score of the tool. Moreover, the study shows the absence of differences attributed to ‘Training’ variable except for the ‘self- awareness’ factor. Where the differences came in favor of the participants who received the ‘Training’; scoring the ‘HIGHER’ arithmetic Mean compared to the Non- trained ones. Last but not least, the study proves that there is no marked differences due to ‘years of experience’ variable. Finally, the study recommends more studies on emotional intelligence for the ‘staff members- administrators and leaders’ at the Ministry of Education- Bahri locality. Moreover, it recommends the upmost utility of the findings of this study to direct the emotional intelligence of the school teachers in order to improve their professional performance. Work- shops for training Ministry of Education employees on emotional intelligence are highly recommended by this study.